Productivity, profitability and energy budgeting of maize (Zea mays)/ greengram (Vigna radiata) intercropping system under rainfed conditions of Eastern Himalayan Region - BAISHYA, L K; ANSARI, M A; WALLING, I; SARMA, P K; PRAKASH, N (The Indian Journal of Agricultural Sciences, 2014)
A field experiment was conducted at Nagaland during 2009 and 2010 to study the productivity, profitability and energy budgeting of maize [Zea mays (L.)]/greengram [Vigna radiata (L.) Witczek] intercropping system under rainfed conditions of Eastern Himalayan Region on a sandy loam soil. There was significant superiority in growth and yield attributes as well as yield of maize (3.37 tonnes/ha) and greengram (1.34 tonnes/ha) under sole cropping as compared to their intercropping system. Maize equivalent yield (5.64 tonnes/ha) land equivalent ratio (1.43), Area Time Equivalency Ratio (1.19), Land Equivalent Coefficient (0.49), and Monetary Advantage Indices (` 3 273) was significantly higher with intercropping system (1:1, closely followed by 1:2 ratio) over other intercropping system under study. Moreover, higher Crop Performance Ratio (3.81) was recorded with 1:3 maize–greengram intercropping system. Intercropping system recorded the higher net return and B: C ratio as compared to either of the sole cropping. Among different row proportions, 1:1 row ratio recorded maximum energy efficiency (19.1) and energy productivity (1569.4 g/MJ) than other intercropping system.